Profitability, Leverage, and Firm Value: Evidence from Retail Companies in the Consumer Cyclical Sector - Pebriyani Pebriyani; Tia Apriani; Nindi Puspitasari; Iswanto Iswanto (Journal of Business Economics : Needs, Services, and Money, 2026)
This study aims to determine and analyse the effect of profitability and leverage on firm value, with firm size as a moderating factor. The population in this study were companies in the consumer cyclical retailing sub-sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sampling method used was purposive sampling. The resulting sample consisted of 11 companies. The data analysis techniques used were panel data regression and moderated regression analysis. The sample processing technique used E-views version 12. The results showed that profitability affected firm value, while leverage and firm size did not. Firm size moderated the effect of profitability on firm value. However, firm size did not moderate the effect of leverage on firm value.